Does equity-based financing improve the performance of banking institutions: a case of Islamic banks? - Shahari, Farihana; Rahman, Md. Saifur (Kuala Lumpur International Business Economics & Law Conference (KLibel), 2019)
This paper explores the possible implications of PLS theory and examines whether the PLS financing instrument can increase the profitability of global Islamic banks. PLS financing instrument is the focus variable, while bank-specific and macroeconomic variables are considered as the controlled variable to draw a reliable and unbiased result. The study undertakes several hypotheses and employs a two-step system GMM estimation technique. The results offer several outcomes; the PLS financing instrument improves the profitability of Islamic banks. The bank-specific and macroeconomic variables have a mixed effect on profitability. The study suggests policy implications to the Islamic banks for sustaining in the competitive banking industries.